MoS2 functionalized AlGaN/GaN transistor based room temperature NO2 gas sensor - Sharma, Nipun; Kumar, Sumit; Gupta, Ankur; Dolmanan, Surani Bin; Patil, Dharmraj Subhash Kotekar; Tan, Swee Tiam; Tripathy, Sudhiranjan; Kumar, Mahesh (Sensors and actuators. A. Physical., 2022)
The ability to monitor toxic gases under room-temperature conditions, with enhanced response and selectivity present in the atmosphere, is still considered as a technical challenge. In this context, we have fabricated AlGaN/GaN high electron mobility transistors (HEMTs) based sensors incorporating molybdenum disulphide (MoS2) functionalization for very sensitive, selective, and quick measurement of even trace amounts of hazardous NO2 gas in the ambient under room-temperature conditions. MoS2 structures with vertically aligned flower-like structure were synthesised using a simple hydrothermal technique and applied to the gate region of AlGaN/GaN HEMTs. The electrical characterisations of MoS2 functionalized AlGaN/GaN HEMTs are then used to detect the presence of NO2 gas. The fabricated sensor showed an enhanced relative sensing response in the range of 40.5–56.7% for 1–100 ppm NO2 gas with complete recovery to 1 ppm NO2 concentration under room-temperature conditions (25ᵒC) without applying any external thermal or optical stimuli. Furthermore, the cyclic and selectivity tests were performed and we found our sensor to be highly selective towards NO2 gas among various other gases. The experimental results showed that MoS2 had excellent properties for NO2 gas detection when used on such GaN-based sensing platform. These findings may be attributed to the exposed edge sites of MoS2 which compliment with configurations with sulphur and the chemisorption phenomenon on its surface that results in altering the drain to source current (IDS) of the HEMT at a constant drain to source voltage (VDS) of 0.5 V. These findings suggest that gas sensors based on the AlGaN/GaN HEMT structure appear to be a promising candidate for the advancement of application potentials of nitride-based integrated electronics. [Display omitted] •A MoS2 functionalized AlGaN/GaN HEMT has been fabricated for detecting NO2 gas molecules.•The structural characterization confirms the flower-like structures of MoS2 synthesized via hydrothermal technique.•The response value of the fabricated sensor is ~56 % at 100 ppm of NO2 at room-temperature.•The key sensing mechanism is the variation of the Schottky barrier height in response to gas exposure.